2020
DOI: 10.3389/fgene.2020.548559
|View full text |Cite
|
Sign up to set email alerts
|

The Co-existence of ADHD With Autism in Saudi Children: An Analysis Using Next-Generation DNA Sequencing

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is one of the most common neurodevelopmental disorders. Several studies have confirmed the co-existence of other neuropsychiatric disorders with ADHD. Out of 106 individuals suspected to have ADHD, eight Saudi Arabian pediatric patients were diagnosed with ADHD using a dual assessment procedure based on highly significant scores from the international criteria for diagnosis; (full form DMS) DSM-5. Then, these patients were examined for the co-existence of autism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Increased expression of IL16 is found in patients with spinal cord injury and Alzheimer’s disease (Di Rosa et al , 2006; Bank et al , 2015). Rare and novel variants of IL16 are identified in Saudi Arabian patients with attention-deficit/hyperactivity disorder (Bogari et al , 2020). It is noted that singleton novel rare loss copy number variation in IL16 is associated with ASD (Prasad et al , 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of IL16 is found in patients with spinal cord injury and Alzheimer’s disease (Di Rosa et al , 2006; Bank et al , 2015). Rare and novel variants of IL16 are identified in Saudi Arabian patients with attention-deficit/hyperactivity disorder (Bogari et al , 2020). It is noted that singleton novel rare loss copy number variation in IL16 is associated with ASD (Prasad et al , 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Third, the 64 bp deletion overlaps with the NCK (non-catalytic region of tyrosine kinase adaptor) associated protein 5 ( NCKAP5 ). This protein-coding gene is uncharacterized but associated with attention deficit-hyperactivity disorder [ 46 ] and drug-induced lupus erythematosus in humans [ 47 ]. Last, mutation cluster 2 overlaps with the solute carrier family member 2 ( SLC14A2 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a different study, intronic SNV rs4675502 of PARD3b was found to be associated with autism spectrum disorder (Anney et al, 2010(Anney et al, , 2012. In another study, missense SNV rs80119103, which causes a Pro1145His mutation in PARD3b at the C-terminus that is not conserved with PARD3, was found in 1 of 8 Saudi children with attention-deficit/hyperactivity disorder (Bogari et al, 2020).…”
Section: Neuropsychiatric Disorders Pard3 and Pard3bmentioning
confidence: 95%